Word reading aloud skills: their positive redefinition through ageing - Chapleau, Marianne; Wilson, Maximiliano A.; Potvin, Karel; Harvey‐Langton, Alexandra; Montembeault, Maxime; Brambati, Simona M. (Journal of research in reading, 2017)
Background Successful reading can be achieved by means of two different procedures: sub‐word processes for the pronunciation of words without semantics or pseudowords (PW) and whole‐word processes that recruit word‐specific information regarding the pronunciation of words with atypical orthography‐to‐phonology mappings (exception words, EW). Methods We compared reading abilities between 35 young and 35 older adults in an experimental reading task including low‐frequency regular (RW), EW and PW. Results A significant effect of word type, group and an interaction word type by group was found for errors. Young adults made significantly more regularization errors than older subjects for EWs. Conversely, young readers read PW and RW significantly faster. These results indicate that older adults compared with younger adults are more accurate when reading low‐frequency EW. Conclusion The fact that young adults were faster than the elderly for PW and RW reading, together with a larger number of regularization errors in EW reading, suggests that they relied on sub‐word processes to a larger extent than the older group. Highlights What is already known about this topic: Sub‐word processes are based on the use of consistent or regular orthography‐to‐phonology mappings that represent the sub‐units that compose words and are mainly used for pseudoword reading. Whole‐word processes use item‐specific information regarding the pronunciation of a particular word and are mainly used for exception word reading. During reading acquisition, and as reading experience increase, children switch from sub‐word processing strategies to a more efficient use of whole‐word processes. What this paper adds: The ability to read exception words continues to improve over the lifespan, even in later stages of life. Elderly adults rely on whole‐word processes to a larger extent than younger adults. Implications for theory, policy or practice: These results contrast with the general idea that ageing is associated with general cognitive decline, so older people should be encouraged to engage in reading activities. The fact that this cognitive ability is improved during ageing could provide insightful information for developing intervention programmes in patients with acquired reading disorders.